Atlantic Cod (Gadus morhua L.) Broodstock Nutrition: The Role Of Arachidonic Acid And Astaxanthin As Determinants Of Egg Quality - Sawanboonchun, Jarin (University of Stirling, 2009)
Cod hatcheries rely greatly on wild-caught broodstock as egg quality from farm-reared broodstock tends to be poor. Broodstock diet and levels of essential fatty acids have been linked to fecundity and egg quality in cod. Arachidonic acid (ARA) and astaxanthin (Ax) are important nutrients linked to fish egg quality and differences in levels have ben found between eggs from wild and farmed cod. The aim of this thesis was to investigate the impact of dietary supplementation with ARA and Ax on fecundity and egg quality in cod. The first experiment investigated the effect of feeding a diet supplemented with ARA, for 1, 2 or 3 months prior to peak spawning. Results showed that supplementation increased ARA in eggs and that Groups fed the supplement had improved fecundity and egg quality (though with no correlation between the duration of supplementation and number/quality of eggs). The second experiment investigated the effect of supplementation of Ax in broodstock diets on egg quality in farmed cod and showed that Ax was taken up into eggs and that fish fed supplemented diet had improved fecundity and egg quality. The third experiment compared the effect of diet supplementation with ARA and Ax on egg quality in wild and farmed cod and showed that despite the dietary supplementation, wild origin fish performed better on a number of egg quality and fecundity indices. However, it was not possible to take the greater ages and spawning experience of the wild broodstock into account, which may have influenced the results. The fourth experiment measured lipid and fatty acid profiles of eggs from two UK cod hatcheries. Variation was found between farms and across seasons. Results showed that supplementation of cod broodstock diet with ARA and Ax had a positive impact on egg quality and fecundity, although effects were not consistent across all egg quality parameters.